Investigation of the overall stability of welded I-beams with a cross-corrugated wall of the Zeman range - S. A. Makeyev; N. G. Silina; M. A. Stupin (Вестник СибАДИ)
Introduction. Welded I-beams with a transversely corrugated wall when loaded in the wall plane are calculated for overall stability in accordance with paragraph 20.6.3.11 of СП 294.1325800.2017, change 2 from 06/15/2021. Here, a separate centrally compressed girder belt is calculated for overall longitudinal stability from the plane of the beam wall as an element pivotally supported at the ends. This does not take into account the joint work of the compressed belt with the wall, supporting ribs, stretched belt.The authors set a goal to show by calculation using the examples of six beams that if, in comparison with the calculation according to СП 294.1325800.2017, the joint work of the compressed belt with the wall, support ribs, stretched belt is taken into account, then the calculated critical load of the total loss of stability of the corrugator will be greater. And this increase is the more significant, the lower the height of the corrugator. At the same time, the authors limited themselves to considering beams with a ratio of sizes and critical loads that ensure the operation of steel in the elastic stage with loss of overall stability.Materials and methods. The general stability of split beams with a transversely corrugated wall was studied by calculation in three ways: according to СП 294.1325800.2017, in the LIRA-CAD PC by modelling beams with shell elements, including belts, walls and support ribs, and according to CП 16.13330.2017, considering a welded I-beam with a flat wall equivalent to the criterion of general stability.The results of the study. The data of calculation of critical loads of the first form of loss of general stability of six split beams of the Zeman range with height are given 333, 500, 750, 1000, 1250, 1500 with a span of 6.0 m in three proposed ways with loading of the upper belt with a uniformly distributed load in the wall plane without loosening the compressed belt in the span and loosening the support sections from the wall plane and from rotation relative to the axis of the beams.Discussion and conclusions. For beams with a wall height of 333 mm, taking into account the joint work of the compressed belt with the wall, stretched belt, support ribs showed an increase in critical load in comparison with the calculation according to СП 294.1325800.2017 by 24%. With an increase in the height of the beams to 900-1000 mm, the difference in the values of critical loads calculated taking into account the joint work of the beam elements and according to СП 294.1325800.2017 non-linearly decreases to 3%. And for corrugated rollers with a height of 1000-1500 mm, this difference is less than 3%, which shows that it is possible to perform calculations of beams with a transversely corrugated wall of the Zeman range with heights of 1000-1500 mm for overall stability with sufficient accuracy for engineering calculations according to СП 294.1325800.2017.